Morphometric and taxonomic studies of Senna ser. Coriaceae (Leguminosae, Caesalpinioideae, Cassieae), including a new species from Chapada Diamantina, Bahia, Brazil - de Lima, Alexandre Gibau; de Freitas Mansano, Vidal; Trovó, Marcelo; Bacon, Christine D. (Revista brasileira de botânica, 2025)
Senna sect. Chamaefistula ser. Coriaceae is restricted to Brazil and is predominantly distributed in savanna habitat. The species are morphologically characterized by their shrub or treelet habit, usually reniform stipules, extrafloral nectaries usually positioned on the middle or distal part of the petiole, zygomorphic corolla and laterally compressed fruits with the seeds parallel to the fruit valves. Previous taxonomic studies have recognized only three species and one variety, nevertheless, they provided the groundwork for a more comprehensive treatment, presented here. Based on fieldwork and on the analysis of herbarium specimens, we recognize five species belonging to Senna ser. Coriaceae including one new species from the seasonally dry areas in the Chapada Diamantina, Senna diamantinensis . We carried out a morphometric analyses and here recognize S. caesia as a distinct species rather than a variety of S. corifolia . We propose a new combination for Cassia kuhlmannii and recognize it under the genus Senna . In addition, we propose two first-step lectotypifications and one second-step lectotypification. The taxonomic treatment provided here includes an identification key, morphological descriptions, taxonomic notes, illustrations, preliminary conservation assessments, and habitat and phenology data for each species.